Penerapan Isi Materi Ajar “Al-Kulliyatu Al-Khamsah” Pada Mata Pelajaran PAI di Keseharian Peserta Didik (Tinjauan Analisis Evaluasi Sumatif) - Nasiruddin Sidqi; Sayid Ahmad Ramadhan; Santiani Santiani; Triwid Syafarotun Najah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
The purpose of the study was to find out and describe the application of the content of teaching materials al-kulliyatu al-khamsah sub-section of maintaining the soul (al-nafs) carried out by students in the school environment. Field research is used as a type of research with the results presented descriptively. The data collection methods are: observation, interviews and documentation followed by validation steps with trianggulation of techniques and sources and analysis stages, namely: data reduction, data presentation, and conclusions.The results showed that class XI students majoring in Multimedia B (MM B) SMK Karsa Mulya Palangka Raya Class XI already knew and understood the orientation and purpose of the content of the teaching material al-kulliyatu al-khamsah sub-section of maintaining the soul (al-nafs). For implementation is carried out in the following way: a. dispose of garbage in its place, b. always actively participate in mutual aid activities to clean and organize the school environment on the third Friday of every month, c. carry out class hygiene picket duties according to a mutually agreed schedule and d. alert each other if one of their friends displays destructive behavior to the school environment. The encouragement or trigger for the realization of the content of teaching material can be classified into two types, namely: a. indeed comes from the awareness within oneself that cleanliness is a mandatory thing that must be done and b. must first be reminded by the teacher and other friends and then want to do so for reasons depending on mood (desire) and imitate a handful of other students (one class and/different classes) with him. Then for the impact felt, namely to arouse their enthusiasm to pay more attention to the conditions of the surrounding environment while always being maintained, including when at school and as a form of application of Islamic religious shari'a which if done is worth a worship.